Quantitative Structure Activity Relationships Studies on Benzimidazole Derivatives as antibacterial agents against Escherichia coli - Sachan, Shailja; Mishra, Aradhana; Tiwari, Santosh; Tiwari, Santosh Kumar; Pandey, Vikash (IJRDO-Journal of Applied Science, 2015)
In a continuing effort to develop novel Benzimidazoleendowed with better pharmacological profiles. A series of Benzimidazolederivatives were designed on the basis of previously developed QSARs.These drugs offer novel mechanisms of action and expanded spectrumsof activity over traditional treatment option. However, with these newagents comes the need for increased awareness of the potentialinteractions and toxicities associated with these drugs. The best modelsfor different antibacterial agents against Escherichia coli were firstvalidated by leave-one-out cross validation procedure. It was revealedthat topological, physicochemical and indicator parameters were foundto have overall significant correlationship with antibacterial activityagainst Escherichia coli and these studies provide an insight to designnew molecules.